2001
DOI: 10.1590/s1517-83822001000100013
|View full text |Cite
|
Sign up to set email alerts
|

Time course of virus-like particles (VLPs) double-stranded rna accumulation in toxigenic and non-toxigenic strains of Aspergillus flavus

Abstract: Two strains of Aspergillus flavus, non-toxigenic NRRL 6550 and toxigenic NRRL 5940, were studied over a period of 44 days, in order to detect the presence of virus-like particles (VLPs) by means of electron microscopy (EM) and nucleic acids electrophoresis. Only the toxigenic strain contained VLPs, presenting three-segmented dsRNA. An increase in VLPs number was observed during the exponential phase of fungal growth, up to day 12 of culture; after this, higher levels of aflatoxin production in toxigenic NRRL 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Mycovirus-encoded killer toxins or peptides have been demonstrated to control fungal infections, including aspergillosis in animals [ 19 ]. In A. flavus , mycovirus infection induced the production of toxigenic aflatoxins [ 20 , 21 ]. Similar results were obtained in partitivirus-transfected A. ochraceus strain overproducing ochratoxin A (OTA) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mycovirus-encoded killer toxins or peptides have been demonstrated to control fungal infections, including aspergillosis in animals [ 19 ]. In A. flavus , mycovirus infection induced the production of toxigenic aflatoxins [ 20 , 21 ]. Similar results were obtained in partitivirus-transfected A. ochraceus strain overproducing ochratoxin A (OTA) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies attempted to identify mycovirus‐mediated mechanisms involved in the qualitative or quantitative production of aflatoxins in A. flavus . Initially, a possible correlation between the presence of a Chrysovirus and the production of aflatoxins in A. flavus NRRL5565 (Schmidt et al ., ) was observed but was not confirmed in the same or different virus‐host systems (Elias and Cotty, ; Silva et al ., ; Kotta‐Loizou and Coutts, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the dsRNA elements and the VLPs could not be detected in young mycelia (<48 h growth) and hyphal tips, it was suggested that at least some of these viruses multiply during the later phases of the fungal life cycle (Varga et al, 1994 ). In contrast, Silva et al ( 2001 ) report that in A. flavus strain NRRL 5940 the number of viral particles increased during the exponential phase of growth and decreased during the later phases. No association between the presence of dsRNAs and the isolates' mitochondrial RFLP haplotype (van Diepeningen et al, 2006 ), specific conserved surface protein types or mating type MAT1-1 and MAT1-2 (Refos et al, 2013 ) have been observed.…”
Section: Incidence Of Mycoviruses In Aspergillimentioning
confidence: 88%
“…In A. flavus strain NRRL 5565, the production of carcinogenic aflatoxins was shown to be repressed by the presence of a mycovirus (Schmidt et al, 1986 ). Similarly, in strain NRRL 5940, aflatoxin production occurred in parallel with decreased presence of viral particles (Silva et al, 2001 ). However Elias and Cotty ( 1996 ) reported that there was no correlation between the presence of dsRNA and the production of aflatoxin in other A. flavus isolates.…”
Section: Effects Of Mycoviruses On the Fungal Hostmentioning
confidence: 93%
See 1 more Smart Citation